Handshake, No. 12 (January 2014) - International Finance Corporation (Washington, DC, 2015)
This issue of the Handshake, IFCs quarterly journal on public-private partnerships, contains the following topics of interest: weighing the options: burn or bury?; waste and climate: supporting governments; community engagement: integrating Indias informal sector; an interview with the director of the documentary Trashed; and bonus: podcast with 2013 CNN hero on community cleanups.